Treatment of varicose ulcer with unna boot: Adverse effects arising from lack of knowledge in its maintenance (Research, Society and Development, 2022)
Objective: To report a clinical case about the inadequate application of inelastic compression therapy (unna boot) and its adverse effects in the treatment of varicose ulcer. Methodology: This is a clinical case report of a descriptive analytical nature, carried out in a program for the treatment of users with venous ulcers and diabetic foot, this being, non-profit and located in the Agreste of Alagoas in the Arapiraca City. The user's permission was acquired through the Free and Informed Consent Term (FICT) according to resolution 196/96. Case report: M.I.C. user, female, 76 years old, diabetic, hypertensive and with venous ulcer in the right lower limb in the anterior tibial region and lateral region of the malleolus. User arrives at the service with signs of inadequate bandage application, causing bruises and blisters due to excessive compression of the limb. Final Considerations: Upon identifying these signs, interventions were carried out, such as suspension of the use of the inelastic bandage so that there is an improvement of the harmful signs caused by the incorrect application of the Unna Boot, health education for the user and companion, as well as contact with the same for weekly monitoring the evolution of the venous ulcer through a photographic record. In this way, there was a significant improvement in the lesion, and an improvement in the user's quality of life.